Electromagnetic energy around Hertzian dipoles. - Schantz, Hans Gregory (IEEE Antennas & propagation magazine.)
This paper considers the behavior of electromagnetic energy around Hertzian dipoles. The method of ?causal surfaces? (surfaces through which there is no net flow of electromagnetic energy) is used to partition and track the energy. A variety of examples, involving both transient and harmonic time dependence, are presented, to illustrate the way in which static and/or reactive energy is converted to outgoing, uncoupled, ?radiated? energy around a Hertzian or point dipole. The principal conclusion is that although accelerating charge may be thought of as the source of the radiation fields, the source of the radiated energy lies in the static and/or reactive field energy near an antenna, and not ?in? or ?on? an antenna itself.